Blood Tablet Giving Program Against Nutritional Status of Senior High School Students - Edi Lesmono (JUMP Health (Journal of Ultimate Public Health), 2020)
Anemia is a problem of micronutrients that are prevalent throughout The world, especially in developing countries are estimated to occur in 30% world population.